2021
DOI: 10.1186/s12934-021-01590-7
|View full text |Cite
|
Sign up to set email alerts
|

Combining transposon mutagenesis and reporter genes to identify novel regulators of the topA promoter in Streptomyces

Abstract: Background Identifying the regulatory factors that control transcriptional activity is a major challenge of gene expression studies. Here, we describe the application of a novel approach for in vivo identification of regulatory proteins that may directly or indirectly control the transcription of a promoter of interest in Streptomyces. Results A method based on the combination of Tn5 minitransposon-driven random mutagenesis and lux reporter genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…As we were unable to find any previous studies that had utilized transposon mutagenesis in the genus Nocardia, we looked to systems that had been used in the closely related and better studied Streptomyces. Previous work showed that a codon-optimized hyperactive variant of the transposase Tn 5 could be used to successfully mutagenize Streptomyces species. Due to our previous work adapting Streptomyces genetic elements to function in Nocardia, , Tn5’s preference for high-GC regions of DNA, and similarity in codon usage and GC content between Streptomyces and Nocardia, we hypothesized that this Streptomyces codon-optimized Tn 5 may also function in the Nocardia. Utilizing the vector pHL734, we performed multiple rounds of transformation of N.…”
Section: Resultsmentioning
confidence: 99%
“…As we were unable to find any previous studies that had utilized transposon mutagenesis in the genus Nocardia, we looked to systems that had been used in the closely related and better studied Streptomyces. Previous work showed that a codon-optimized hyperactive variant of the transposase Tn 5 could be used to successfully mutagenize Streptomyces species. Due to our previous work adapting Streptomyces genetic elements to function in Nocardia, , Tn5’s preference for high-GC regions of DNA, and similarity in codon usage and GC content between Streptomyces and Nocardia, we hypothesized that this Streptomyces codon-optimized Tn 5 may also function in the Nocardia. Utilizing the vector pHL734, we performed multiple rounds of transformation of N.…”
Section: Resultsmentioning
confidence: 99%
“…However, the biggest challenge of the mutagenesis strategy is the high throughput but efficient screening of strains for hyper-production of the desired natural products. To overcome this obstacle, many reporter systems have been developed in Streptomyces , such as chromogenic strategies with enzymes IdgS and XylE to produce the blue and yellow pigments ( Li et al, 2015 ; Li et al, 2018 ), respectively, and antibiotic resistance to kanamycin ( Li et al, 2018 ; Gongerowska-Jac et al, 2021 ). However, false positives frequently arise in single-reporter systems, because different disturbances might result in the same reporter phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, dual reporter systems have been preferentially used to more efficiently obtain the desired mutants ( Xiang et al, 2009 ). The reporter systems are usually designed linked to the target promoters for screening of improved transcriptional strength, but mostly on the replicative plasmids or integrated in the genome distant from the native promoters of the biosynthetic gene cluster ( Gongerowska-Jac et al, 2021 ). Probably due to the influence of genomic locations or the incompleteness of transcriptional elements on the cloned promoter ( Bilyk et al, 2017 ), the strength of the reporter system does not always correlate well with the productivity of natural products.…”
Section: Introductionmentioning
confidence: 99%
“…mutants of regulatory genes) can be labour intensive and therefore prevents high-throughput screens. To overcome these challenges, various studies have combined reporter plasmids with the use of transposon mutagenesis [20–22]. Specifically, mutant generation is frequently performed in the parental strain harbouring the reporter plasmid, presenting technical challenges during library preparation, and necessitating sequencing of strains identified in the screen.…”
Section: Introductionmentioning
confidence: 99%